PENGARUH RASIO KEUANGAN, KEPEMILIKAN INSTITUTIONAL, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN, KUALITAS AUDIT, OPINI TAHUN SEBELUMNYA TERHADAP OPINI GOING CONCERN - , FITRI DWI JAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to examine the effect of financial ratio, institutional ownership, managerial ownership, independent commissioner, audit quality, the previous year opinion about going concern opinion. This research used a sample of manufacture companies which are registered in Indonesia Stock Exchange during 2008 until 2012 period. There are 30 companies used as the sample of the research with an observation period of 5 years. Based on the purposive sampling method, the total of the research sample is 150. The dependent variable of the research is going concern opinion. The independent variable of the research is financial ratio, institutional ownership, managerial ownership, independent commissioner, audit quality, the previous year opinion. The hypothesis was examined using regression logistic (Binary Logistic). The result of the research shows that the financial ratio measured by the liquidity ratio, the leverage ratio, the profitability ratio, the growth ratio, the institutional ownership, the managerial ownership, the independent commissioner, the audit quality, and the previous year opinion did not affect the going concern opinion. Keywords : Going Concern Opinion, Current Ratio, Debt to Equity, Return on Asset, Sales Growth, Institutional Ownership, Managerial Ownership, Independent Commissioner, Audit Quality, The Previous Year Opinion